Bilateral knee extensor disruption in severe crouch gait. (27th June 2013) - Elhassan, Yahya; Kiernan, Damien; Lynch, Tim; Brien, Tim O
Abstract : Crouch gait is one of the most troublesome abnormal gait patterns in ambulant patients with spastic diplegic cerebral palsy (CP). Although CP is a non-progressive condition, crouch gait can result in knee extensor disruption (KED) causing deterioration or cessation of ambulation. Diagnosis of KED in crouch gait is often overlooked. We report a seminal case of a 28-year-old active woman with diplegic CP with severe crouch gait who was referred for gait analysis due to subjective decreased walking speed and endurance. Gait analysis showed kinematic features typical of KED and radiology confirmed the diagnosis.